2004
DOI: 10.1080/00288233.2004.9513579
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants in blood from sheep lines divergently selected for facial eczema resistance

Abstract: Romney sheep have been evaluated for resistance to facial eczema (FE) using a process which involves challenge with the FE toxin, sporidesmin, and they have been bred in selection lines for increased resistance (R) or susceptibility (S) to FE. There is evidence that sporidesmin exerts its toxic effects by generating reactive oxygen species, and protection can be afforded by a number of antioxidants and antioxidant enzymes. Our objective was to summarise three separate experiments to determine whether the R and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…In our comparative studies of antioxidant enzymes in blood of FE‐resistant vs. FE‐susceptible selection lines, we detected significantly higher catalase and glutathione peroxidase activities in the former animals (Hohenboken et al . ). In contrast, we observed significantly higher superoxide dismutase activity in blood of susceptible rather than resistant animals; this enzyme was presumably superoxide dismutase 3, extracellular (encoded by SOD3 ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In our comparative studies of antioxidant enzymes in blood of FE‐resistant vs. FE‐susceptible selection lines, we detected significantly higher catalase and glutathione peroxidase activities in the former animals (Hohenboken et al . ). In contrast, we observed significantly higher superoxide dismutase activity in blood of susceptible rather than resistant animals; this enzyme was presumably superoxide dismutase 3, extracellular (encoded by SOD3 ).…”
Section: Discussionmentioning
confidence: 97%
“…The animals also were used to explore the mechanism of resistance by comparing the serum levels of antioxidant enzymes between the lines (Hohenboken et al . ). In genetic studies, these selection lines were used in three different types of experiments aimed to detect causative FE genes and loci.…”
Section: Introductionmentioning
confidence: 97%
“…Hohenboken et al . () reported in sheep that the activity of SOD1 was lower in facial eczema‐resistant selection‐line animals than in susceptible‐line animals. SOD1 is located on BTA1 where no QTL were found.…”
Section: Discussionmentioning
confidence: 98%
“…Munday et al (1983) demonstrated that liver injury by sporidesmin in sheep could be reduced by giving exogenous antioxidants. Hohenboken et al (2004) examined the possibility that heritable facial eczema resistance might be the consequence of levels of blood antioxidants and antioxidant enzymes which differed significantly between selection lines of sheep. The authors concluded that "divergences between resistant and susceptible sheep were not large enough to be a reliable indicator of individual FE resistance.…”
Section: Mechanism Of Toxicity Of Sporidesminmentioning
confidence: 99%